2021
DOI: 10.1186/s12893-021-01264-6
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors of surgical site infection after hysterectomy for endometrial carcinoma: a retrospective analysis

Abstract: Background Surgical site infection (SSI) is a common postoperative complication. We aimed to analyze the potential risk factors of SSI in patients with endometrial carcinoma. Methods Patients with endometrial carcinoma who underwent surgery treatment in our hospital from Sept 1, 2018 to August 31, 2020 were included. We retrospectively compared the characteristics of SSI and no SSI patients, and logistic regression analyses were performed to identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 37 publications
0
9
1
Order By: Relevance
“…Surgical site infection rates in patients after gynecological surgeries in different regions and hospitals vary according to data volume, surgical skills, and wound infection prevention and control measures [ 11 ]. Several studies have shown that surgical site infection rates in gynecological surgeries are 1–14.47% [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Surgical site infection rates in patients after gynecological surgeries in different regions and hospitals vary according to data volume, surgical skills, and wound infection prevention and control measures [ 11 ]. Several studies have shown that surgical site infection rates in gynecological surgeries are 1–14.47% [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Expert judgment, extensive literature studies, and the availability of clinical data were used to select all possible candidate predictors for potential operative site infections in gynecologic oncology patients ( 5 9 ). The following candidate predictors were included in the study: general information [age, body mass index (BMI), season of admission, surgical history in recent 3 months, comorbidities, and the age-adjusted Charlson Comorbidity Index (aCCI)], preoperative variables [FIGO stage, ASA class, site of cancer, Barthel Index, Morse Fall Scale (MFS) score, preoperative steroid use, laboratory values, preoperative hair removal, preoperative length of stay (LOS), antibiotic prophylaxis within 0.5–1 h before operation, and the modified surgical complexity score (MSCS)], and intraoperative variables (surgical approach, operative time, estimated blood loss, blood transfusion, emergent surgery, and NNIS index).…”
Section: Methodsmentioning
confidence: 99%
“…On the basis of different inclusions of variables, we have developed three models to predict the potential operative site infections in a gynecologic oncology surgery:(a) candidate predictor for Model 1 was limited to only the NNIS risk index; (b) candidate predictors for Model 2 included all factors indicated in Table 1 except GNRI; (c) candidate predictors for Model 3 included all variables listed in Table 1 . To select the most optimal predictive features from the candidate predictors, the least absolute shrinkage and selection operator (LASSO) method was performed using the R package glmnet ( 9 ). This method is well-suited for reducing large datasets and reducing the likelihood of collinearity between the variables obtained from the same subject.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Frailty has been connected to advancing age and has been demonstrated to increase postoperative complications and mortality following gynecologic surgery. Given that uterine corpus cancer is a common reason for hysterectomy, with an age-standardized rate of 12.9 per 100 000 women in rich nations, the additional burden on communities could be significant [5].…”
Section: Introductionmentioning
confidence: 99%